2010
DOI: 10.1097/scs.0b013e3181d879fa
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Dental-Arch Morphology in Adult Unoperated and Operated Cleft Palate Patients

Abstract: The influence of cleft palate on the development of maxillary arch is limited to the vicinity of the cleft in the anterior region only. Palatoplasty is the main cause resulting in the constriction of maxillary arch, while inhibiting the sagittal development of the anterior arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 2 publications
1
17
0
3
Order By: Relevance
“…This suggests that the vomer in the UCLP group has an intermediate morphology between those in the BCLP and Control groups. The short upper dental arch length reported by Ye et al 13 supports this.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that the vomer in the UCLP group has an intermediate morphology between those in the BCLP and Control groups. The short upper dental arch length reported by Ye et al 13 supports this.…”
Section: Discussionsupporting
confidence: 77%
“…rotated clockwise and the anterior part collapsed according to the fitting curve of the dental arch; the overall dental arch showed a ''V'' shape. Ye et al 19 reported a similar conclusion by measuring the dental cast CT. We also found that the UCLP patients have a more constrictive arch width than patients in the GIII group. However, the differences of the maxillary dental widths between the GIII and GN groups were not statistically significant.…”
Section: Discussionmentioning
confidence: 51%
“…In previous studies, by dental cast measurement we have found that although patients with unilateral cleft lip and palate (UCLP) have an imminent palatal tissue shortage, surgical cleft palate repair is the main cause of transverse constriction of maxillary arch (Ye et al, 2010(Ye et al, , 2012. In this study, we tried to reveal the influence of cleft palate malformation itself and operation on maxillary sagittal and vertical development, by lateral cephalometric analysis.…”
Section: Introductionmentioning
confidence: 96%